Biomonitoring PhIP, a Potential Prostatic Carcinogen, in the Hair of Healthy Men of African and European Ancestry - Robert J. Turesky; Clarence Jones; Jingshu Guo; Kari Cammerrer; Laura A. Maertens; Emmanuel S. Antonarakis; Zhanni Lu; Logan G. Spector (Toxics)
Heterocyclic aromatic amines (HAAs), formed during the cooking of meat, are potential human carcinogens, underscoring the need for long-lived biomarkers to assess exposure and cancer risk. Frequent consumption of well-done meats containing 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP), a prevalent HAA that is a prostatic carcinogen in rodents and DNA-damaging agent in human prostate cells, has been linked to aggressive prostate cancer (PC) pathology. African American (AA) men face nearly twice the risk for developing and dying from PC compared to White men. We previously demonstrated that scalp hair is a reliable biospecimen for measuring PhIP intake using liquid chromatography-mass spectrometry. This study aimed to determine whether PhIP dietary intake is higher in AA men, potentially contributing to this health disparity. Healthy AA men were found to have a significantly higher mean hair PhIP level (2.12-fold) than White men on free-choice diets. However, this difference was not statistically significant after adjusting for melanin content. Further research is needed to understand how hair pigmentation, follicular density, and other morphological features of hair influence PhIP accumulation. These insights can improve the accuracy of using hair PhIP levels as a biomarker for exposure and its potential associations with cancer risk.